Incidence of hypoparathyroidism after total thyroidectomy using conventional versus harmonic scalpel - Walid R. Abdelaty (Al-Azhar Assiut Medical Journal)
Background As complete thyroidectomies are common procedures, we examine the effects on parathyroid hormone (PTH) levels of using a harmonic scalpel in conjunction with standard techniques. Patients and methods Eighty participants of this prospective, randomized research who had total thyroidectomies in the General Surgery Department were divided into two equal groups at random: complete thyroidectomy was performed with a harmonic scalpel in group I and a standard approach in group II. Results There is a significant correlation between the surgical technique used and the decrease in PTH after surgery. Conclusion If the conventional method was applied following thyroidectomy, there was noticeable decrease in the postoperative serum PTH. When harmonic scalpel is used throughout a thyroidectomy, there is minimal risk of hypoparathyroidism, excellent dissection, and safety.